Design and codifying a test to measure the speed of defensive movements for advanced defender in the defensive formation (5-1) in handball - Khaleel Fathi, Moushriq (International Journal of Psychosocial Rehabilitation, 2020)
The backbone of the defense , which is based on its handball team, so requires all team members to master defensive skills, there are many defensive formations, and what concerns us in this study are formations defense where the team is forced defender to intentionally spread the team in the form of two rows, attempt cut or deflect the ball from team striker, such as defensive formation (5-1), which requires a team that has a player Advanced, has a great deal of intelligence, the correct prediction of the course of play and the movements of the attackers and block their movements, to choose so the player is always done in It is subjective and improvised and often accompanies this process So that the errors had to me was selected e objectively, through standardized testing and be the results of its objective and accurate, so we decided to codify this test, and here comes the importance of this study, the quality of an addition to the trainers and the Federation of Handball and Iraqi clubs